Effectiveness of Weekly Iron and Folic Acid Supplementation Programme to Control Anemia among Rural Adolescent School Girls of Davangere, Karnataka - Navinkumar Angadi; Balu PS (Medsci Publications, 2019)
Introduction: Adolescent anaemia is a critical public health problem in India. The ministry of Health and Family Welfare, government of India has launched the weekly Iron and Folic acid Supplementation (WIFS) Programme to reduce the prevalence and severity of nutritional anaemia among adolescents. Objective: To assess the effectiveness of weekly iron and folic acid supplementation programme to control anemia among rural adolescent school girls in the field practice area of JJM Medical College, Davangere. Methods and materials: A Longitudinal study with Pretest-Posttest Design was conducted in the rural field practice area of JJM Medical College among 175 adolescent school girls. Results: The prevalence of anemia at the baseline was 38% and it reduced to 26% at the end of one year intervention. The mean haemoglobin concentration was increased by 0.37gm/dl. Conclusion: Weekly Iron and Folic acid supplementation and regular deworming programme was beneficial to reduce the prevalence of anaemia and to improve the mean haemoglobin level of the adolescent girls. The supplementation is beneficial to both anaemic and non-anaemic girls. All the age groups were benefited from the programme.